COMPARISON OF MATHEMATICAL STUDENTS OF SMP STUDENTS BETWEEN LEARNING USING A REALISTIC APPROACH WITH USING OPEN ENDED APPROACH - Fathoni Akhmad Ramdhani; Euis Eti Rohaeti ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
This study aims to examine whether improving students' mathematical reasoning abilities that get learning by using a realistic mathematics education approach is better than students who get open ended learning. Method in this research is experiment method by using 2 sample. The sample was taken randomly, that is class VIII-C as a class that get learning by using realistic mathematics education approach, and class VIII-B as a class that get open ended learning. Instrument in this research is a test instrument in the form of description consists of 8 given problem in the form of pretest and postes, then the data of students' mathematical reasoning scores were analyzed by using the normality test of both groups then tested the homogeneity of two variance and the significance test of the difference of two averages. The final result of this study with a significance level of 0.05 concluded that the improvement of capability the mathematical reasoning of students who get learning by using a realistic mathematics education approach is better than students who get open ended learning.